In-depth Analysis of the Discrepancy in Dengue Test Results andAssociation with Various Factors (The Planet, 2024)
Introduction: Dengue fever remains a significant public health challenge worldwide, especially in tropical and subtropical regions. Accurate and timely diagnosis is crucial for effective management and control. This study aims to explore the discrepancies in dengue test results and the association with demographic, symptomatic, and environmental factors. Methods & Materials: This observational study was conducted over six months at Dhaka Medical College, involving 77 participants presenting with symptoms suggestive of dengue. Data were collected on demographic details, clinical symptoms, laboratory parameters, and environmental risk factors. Dengue diagnosis was confirmed using NS1 antigen and IgG/IgM serological tests. Result: The study predominantly involved children aged 6-10 years (33.77%), with a mean age of 8.66±8.73 years, and a higher prevalence of males (55.84%) residing in urban areas (57.14%). A significant majority (89.61%) had no prior dengue infection. The NS1 antigen test was positive in 81.82% of cases, while serological responses varied, with 18.18% IgG positive, 14.29% IgM positive, and 12.99% positive for both. Environmental risk factors such as inadequate mosquito control measures were prevalent (55.84%). Notable laboratory variability suggested acute inflammatory responses, with high mean values in WBC count and serum ferritin levels. A strong inverse correlation was observed between lymphocyte and neutrophil percentages. Conclusion: The study highlighted significant discrepancies in dengue test results influenced by various factors, including environmental risks and laboratory parameters. These findings emphasize the need for comprehensive diagnostic strategies that incorporate both antigen and antibody testing to improve the accuracy of dengue diagnostics and enhance public health interventions.
Keywords: Dengue fever; NS1 Antigen; IgG/IgM; Serological Tests; Diagnostic Discrepancies; Environmental Factors; Laboratory Parameters